Pehr Frigel’s Om Contrapunkten (c. 1815): The Earliest Extant Counterpoint Method in the Swedish Vernacular, Edited and Translated with Historico-Critical Commentary - Lundberg, Mattias (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2012)
This study presents an annotated critical edition of the earliest known counterpoint treatise in the Swedish language, including a translation into English and commentary concerning its sources, context, and intertextual relationships within the counterpoint literature. The treatise is to a considerable extent an adaptation of passages from J. G. Albrechtsberger’s Gründliche Anweisung zur Composition (Leipzig: Breitkopf, 1790) and was written by Pehr Frigel (1750–1842). Frigel was secretary and librarian of the Swedish Royal Academy of Music and professor of music literature, theory and aesthetics at its conservatoire. The evidence presented in this study indicates that the preparation of Om Contrapunkten is closely linked to Frigel’s counterpoint teaching in the early nineteenth century, both at the conservatoire and privately.